KESADARAN HUKUM BERLALU LINTAS PADA PESERTA DIDIK KELAS XI SMK NEGERI 2 KOTA TERNATE - Rusdi Hasan; Faisal Faisal (Universitas Khairun, 2018)
This study aims to determine the legal traffic awareness of first grade students of SMK Negeri 2 Kota Ternate. To find out the understanding or knowledge of students as an effort the traffic police can improve the discipline of motorized traffic. This research was conducted at SMK Negeri 2 Kota Ternate. This study used a qualitative approach with descriptive methods, with the number of respondents is15 students, among them the principal, vice principal of student affairs, vice principal of curriculum, PKN teachers and students. Data collection techniques use observation, in-depth interviews, and documentation. Data analysis in research using data reduction, data presentation, and conclusions. Based on the results of the study, there was a decrease in traffic law awareness. The results of the study showed that traffic legal legal awareness of class XI students of SMK Negeri 2 Ternate is still very low, this was caused because there were several inhibiting factors, among which it indicated that motorists in particular two wheels the whole has started in traffic discipline, is one of the alternative ways to increase legal awareness of traffic discipline of motorized motorbike traffic, especially two-wheeled riders. But in its implementation there are still obstacles faced by the Satlantas Ternate. Among other things, originating from the quality of students (community driving behavior) road arrangement and inadequate traffic signs. Keywords: Legal awareness, student traffic, and SMK Negeri 2 Kota Ternate